Epidemiology of inflammatory bowel disease in the Province of Granada, Spain: a retrospective study from 1979 to 1988. Issue 9 (September 1993) - Martínez-Salmeron, J F; Rodrigo, M; de Teresa, J; Nogueras, F; García-Montero, M; de Sola, C; Salmeron, J; Caballero, M
Abstract : An epidemiological study of inflammatory bowel disease in the Province of Granada, Spain, was conducted between 1979 and 1988. Altogether, 257 cases were identified: 167 ulcerative colitis, 79 Crohn's disease, and 11 indeterminate colitis. The mean incidence of ulcerative colitis in the 10 year period was 2/10(5) and 0.9/10(5) for Crohn's disease. This is the first epidemiological study in Spain of the incidence of ulcerative colitis and corroborates the results of an earlier population based study on the incidence of Crohn's disease in Spain.